Numerical study of behavior raft based on sandy soil subject to seismic loads. - فندو سلمى; توفيق فياض (Latakia University Journal -Engineering Sciences Series, 2025)
The issue of analyzing the behavior of foundations subjected to seismic loads has emerged as an important topic of research over the past years, in view of the large damages caused by earthquakes. Under the influence of seismic loads, foundations are exposed to a decrease in the bearing capacity of the foundation soil, increase settlements, rotation and horizontal slides of the foundation and structures. Experimental and theoretical studies and research have proven that the behavior of foundations changes and the bearing capacity of the soil decreases under the influence of seismic loads. By observing the effects of a number of pervious earthquakes, it was found that some cases of collapse of foundations occurred in locations where the soil was not subject to liquefaction, increased pore water pressure, or loss of slope stability. The main cause of these collapses was explained as a direct result of impermissible settlements and a decrease in the bearing capacity of the soil under the influence of seismic loads. This research deals with a numerical parametric study using the finite element method (FEM), using (Plaxis 3D), the behavior of a raft resting on sandy soil and subject to seismic loads. The research includes conducting a study of the effect of changing the parameters affecting the behavior of the raft and soil (Raft thickness and foundation depth), In order to evaluate the impact of these variables on (Time record of horizontal acceleration with time and vertical displacement with time down the raft). This is with the aim of understanding the response behavior of the raft under conditions of dynamic loading to achieve a stable, low cost, economical raft foundation under the influence of dynamic loads.